R&D Disclosure and Short-Term Investors: Evidence from Mandated Patent Disclosure - Blanco, Iván; García, Sergio J.; Wehrheim, David (The Accounting Review, 2026)
ABSTRACT We examine how the prospect of research and development (R&D) disclosure affects a firm’s institutional investor base. Difference-in-differences (DiD) regressions around the enactment of the American Inventors Protection Act (AIPA), which mandated the public disclosure of patent applications within 18 months of filing, show that short-term institutional investors increase their holdings before public information is released, whereas long-term investors do not adjust their positions. This anticipatory shift is consistent with theoretical predictions that expected disclosure strengthens short-horizon investors’ incentives to acquire and trade on private information. We further document that stock prices reflect more firm-specific information leading up to disclosure and that improved liquidity at disclosure enables short-term investors to partially unwind their positions. Our paper offers novel evidence on how increases in the expected likelihood of disclosure shape investor behavior and the composition of firms’ investor bases.